ASPEK SUFISTIK DALAM NOVEL ASMARALOKA KARYA DANARTO (SUFISTIC ASPECTS IN THE NOVEL ASMARALOKA BY DANARTO) - Ervina Yuni Arianie (Universitas Lambung Mangkurat, 2020)
AbstractSufistic Aspects in the Novel Asmaraloka by Danarto.The purpose of the research inthis thesis is to reveal the sufistic aspects in the novel Asmaraloka by Danarto. Danartois one of the writers who influential in the development of Sufistic literature inIndonesia. Using central themes related to transcendental experience is the inherentcharacteristic of Danarto. By looking at the concept of Danarto's authorship closelyrelated to Tasawuf or Sufism, the Asmaraloka novel cannot be separated from the bondbetween the lover and the Highest Creator. With the setting of a mirage war, Danartocriticizes human nature who are always easy to fight with each other just because ofdifferences. Prolonged war turmoil is as a description of the search for the meaning ofhuman nature. This research is qualitative descriptive research using a Sufistic literaryapproach and assisted by the semiotic theory of Roland Barthes which refers to theavailable signs and markers in the text, which have a correlation to the things outside.The method used is a content analysis method that helps researchers to focus onsubstantial discussions from primary sources supported by secondary data sources. Theprimary data source of this study was the novel Asmaraloka by Danarto which was republishedby Diva Press in 2016. While the secondary data source of this study was inthe form of national and international articles and journals.Key words: character education, semiotic, sufistic, tasawuf, transcendental AbstrakAspek Sufistik Dalam Novel Asmaraloka Karya Danarto. Tujuan penelitian pada tesisini adalah mengungkap aspek sufistik dalam novel Asmaraloka karya Danarto.Danarto merupakan salah satu sastrawan yang berpengaruh pada perkembangansastra sufistik di Indonesia. Mengangkat tema-tema sentral yang berkaitan denganpengalaman transendental menjadi ciri khas yang melekat pada Danarto. Denganmelihat konsep kepengarangan Danarto yang lekat dengan tasawuf atau sufisme, novelAsmaraloka tidak lepas dari ikatan antara sang pencinta dan Yang Maha Pencipta.Berlatar cerita perang fatamorgana, Danarto mengkritisi sifat manusia yang selalumudah bertikai satu sama lainnya hanya karena masalah perbedaan. Kemelut perangyang berkepanjangan sebagai gambaran pencarian makna hakikat manusia. Penelitianini termasuk dalam penelitian kualitatif deskriptif dengan menggunakan pendekatankonsep sastra sufistik, tasawuf dan dibantu teori semiotik dari Roland Barthes yangmengacu pada tanda maupun petanda yang ada dalam teks, yang memiliki korelasipada hal yang berada diluarnya. Metode yang digunakan adalah metode analisis isiyang membantu peneliti untuk fokus pada pembahasan yang substansial dari sumberprimer yang didukung oleh sumber data sekunder. Adapun sumber data primer daripenelitian ini adalah novel Asmaraloka karya Danarto yang diterbitkan ulang olehDiva Press pada tahun 2016. Sedangkan sumber data sekunder penelitian ini adalahberupa artikel dan jurnal nasional maupun internasional.Kata-kata kunci: pendidikan karakter, semiotik, sufistik, tasawuf, transendental